A miR‐34a‐SIRT6 axis in the squamous cell differentiation network. (16th July 2013) - Lefort, Karine; Brooks, Yang; Ostano, Paola; Cario‐André, Muriel; Calpini, Valérie; Guinea‐Viniegra, Juan; Albinger‐Hegyi, Andrea; Hoetzenecker, Wolfram; Kolfschoten, Ingrid; Wagner, Erwin F; Werner, Sabine; Dotto, Gian Paolo
<x xml:space="preserve">Abstract</x> Squamous cell carcinomas (SCCs) are highly heterogeneous tumours, resulting from deranged expression of genes involved in squamous cell differentiation. Here we report that microRNA‐34a (miR‐34a) functions as a novel node in the squamous cell differentiation network, with SIRT6 as a critical target. miR‐34a expression increases with keratinocyte differentiation, while it is suppressed in skin and oral SCCs, SCC cell lines, and aberrantly differentiating primary human keratinocytes (HKCs). Expression of this miRNA is restored in SCC cells, in parallel with differentiation, by reversion of genomic DNA methylation or wild‐type p53 expression. In normal HKCs, the pro‐differentiation effects of increased p53 activity or UVB exposure are miR‐34a‐dependent, and increased miR‐34a levels are sufficient to induce differentiation of these cells both in vitro and in vivo. SIRT6, a sirtuin family member not previously connected with miR‐34a function, is a direct target of this miRNA in HKCs, and SIRT6 down‐modulation is sufficient to reproduce the miR‐34a pro‐differentiation effects. The findings are of likely biological significance, as SIRT6 is oppositely expressed to miR‐34a in normal keratinocytes and keratinocyte‐derived tumours.